Exploring WhatsApp Emoji from Tamizh Culture (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Emojis are evolving as universal language as it is embodied with text messaging. It emphasises the text message as what we could do in interpersonal communication with postures, gestures etc. A set of different symbols available in WhatsApp to add emotions to the text. A symbol is not only representing an object or human emotion, it is part of a culture. People from different culture use different meaning to the symbols and they give their own meaning to a particular symbol which may be differ to another culture. This paper explores the WhatsApp Emojis from Tamizh Culture. Survey method is adopted in order to analyse the usages of WhatsApp Emojis among college students in Chennai. How to cite this article: Sathish R. Exploring WhatsApp Emoji from Tamizh Culture. J Adv Res Jour Mass Comm 2018; 5(4): 109-111. DOI: https://doi.org/10.24321/2395.3810.201827